2018
DOI: 10.5921/yeartradmusi.50.2018.0165
|View full text |Cite
|
Sign up to set email alerts
|

Squaring Off: The Forgotten Caller in Cape Breton Square Dancing

Abstract: Square dancing forms a vibrant part of the traditional music scene in Cape Breton, Nova Scotia. In addition to the weekly West Mabou square dance, monthly dances and occasional square dances can be found across the island year-round. The number of square dances balloons during the summer months. But quite unlike most other square dance traditions in North America, Cape Breton square dancing rarely features a caller, a person who calls out the movements so that dancers do not have to remember them and can focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Milovanovi, D discussed the artistic expression of dance in movies and concluded that it is a positive way to record the art of dance by using film and video animation as a carrier, which is conducive to the dance aesthetics' dissemination and preservation [14]. Sparling, H. describes the current status of square dancing in Cape Breton, Nova Scotia, as part of a traditional folk dance culture characterized by non-standardized movements, with a focus on performance concentration, musical features, and communication between dancers [15]. Digital technology in the information age provides more diverse forms of expression for the creation of Chinese folk dances.…”
Section: Introductionmentioning
confidence: 99%
“…Milovanovi, D discussed the artistic expression of dance in movies and concluded that it is a positive way to record the art of dance by using film and video animation as a carrier, which is conducive to the dance aesthetics' dissemination and preservation [14]. Sparling, H. describes the current status of square dancing in Cape Breton, Nova Scotia, as part of a traditional folk dance culture characterized by non-standardized movements, with a focus on performance concentration, musical features, and communication between dancers [15]. Digital technology in the information age provides more diverse forms of expression for the creation of Chinese folk dances.…”
Section: Introductionmentioning
confidence: 99%